The Views Of Ibn Taymiyya And Ibn Qayyim On The Finitude Of Hell: An Analytical Study And Rebuttals (Eurasian Journal of Humanities and Social Sciences, 2026)
This article provides a comprehensive analysis of the views held by Shaykh al-Islam Ibn Taymiyya and his disciple Ibn Qayyim al-Jawziyya regarding the fana (finitude or eventual disappearance) of Hellfire. The author examines the alignment of these views with the consensus (ijma) of the Ahl al-Sunnah wal-Jama'ah, evaluates the strength of the provided evidence, and reviews the rebuttals issued by contemporary and subsequent scholars, such as Taqi al-Din al-Subki, al-San’ani, and al-Albani. Furthermore, the article analyzes the contradictory passages within the works of Ibn Taymiyya and Ibn Qayyim and discusses the hypothesis that they may have retracted these views toward the end of their lives